PENERAPAN MOBILISASI DINI PADA ASUHAN KEBIDANAN IBU NIFAS UNTUK MEMPERCEPAT PENURUNAN TINGGI FUNDUS UTERI DI PUSKESMAS TANJUNG BALAI KARIMUN - Maryati; Arum Dwi Anjani (Universitas Batam, 2023)
The postpartum period is a critical period for both the mother and the baby. The government has issued programs and technical policies to prevent post partum bleeding, namely at least 4 visits during the puerperium, postpartum visits, postpartum gymnastics, increased maternal nutrition, early initiation of breastfeeding (IMD) and early mobilization. Early mobilization is very important for mothers during the puerperium to accelerate the process of uterine involution. The purpose of writing is to apply early mobilization in midwifery care to accelerate the decrease in the height of the uterine fundus. The type of research used in the preparation of practice reports is descriptive research using the case study method. Data collection methods are participatory observation, interviews, measurements, documentation. The results of the application of midwifery care to Ny. A in the form of early mobilization for postpartum mothers shows that early mobilization helps accelerate the decrease in the height of the uterine fundus. Early mobilization by post partum mothers in the first 6 hours after delivery can help speed up the return of the uterus to its original shape. This is made possible because of the movements made by the mother which help to improve blood circulation and expel lochia so that it helps speed up the process of uterine involution.